PAHs as tracers of the molecular gas in star-forming galaxies - Cortzen, I; Garrett, J; Magdis, G; Rigopoulou, D; Valentino, F; Pereira-Santaella, M; Combes, F; Alonso-Herrero, A; Toft, S; Daddi, E; Elbaz, D; Gómez-Guijarro, C; et al. (Oxford University Press, 2018)
We combine new CO(1–0) line observations of 24 intermediate redshift galaxies (0.03 < z < 0.28) along with literature data of galaxies at 0 < z < 4 to explore scaling relations between the dust and gas content using polycyclic aromatic hydrocarbon (PAH) 6.2 μm (L6.2), CO (⁠L′CO⁠), and infrared (LIR) luminosities for a wide range of redshifts and physical environments. Our analysis confirms the existence of a universal L6.2–L′CO correlation followed by normal star-forming galaxies (SFGs) and starbursts (SBs) at all redshifts. This relation is also followed by local ultraluminous infrared galaxies that appear as outliers in the L6.2–LIR and LIR–L′CO relations defined by normal SFGs. The emerging tight (σ ≈ 0.26 dex) and linear (α = 1.03) relation between L6.2 and L′CO indicates a L6.2 to molecular gas (⁠MH2⁠) conversion factor of α6.2 = MH2/L6.2 = (2.7 ± 1.3) × αCO, where αCO is the L′CO to MH2 conversion factor. We also find that on galaxy integrated scales, PAH emission is better correlated with cold rather than with warm dust emission, suggesting that PAHs are associated with the diffuse cold dust, which is another proxy for MH2⁠. Focusing on normal SFGs among our sample, we employ the dust continuum emission to derive MH2 estimates and find a constant MH2/L6.2 ratio of α6.2 = 12.3 M⊙/L⊙(σ ≈ 0.3 dex). This ratio is in excellent agreement with the L′CO-based MH2/L6.2 values for αCO = 4.5 M⊙/(K km s−1 pc2) which is typical of normal SFGs. We propose that the presented L6.2–L′CO and L6.2–MH2 relations will serve as useful tools for the determination of the physical properties of high-z SFGs, for which PAH emission will be routinely detected by the James Webb Space Telescope.